Molecular and phenotypic investigations of enzyme mediated resistance profiles against aminoglycoside antibiotics in gram-negative clinical isolates in Dhaka, Bangladesh - Hasib, Saad Hassan (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2018.